Relationship between Social Media Dependency, Perceived Parenting Style, Delay of Gratification, and Narcissism - Derebaşı, Muhammet Burak (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Worldwide, there is an increasing interest to study social media dependency. Currently, most of the researches compare social media dependency with other dependencies such as substance abuse and gambling. Although, there is limited research to investigate the effect of personality on social media dependency. Therefore, the main aim of the current study was to examine the predictor roles of narcissism, perceived parenting styles and delay of gratification on social media dependency. A total of 152 women and 146 men aged between 18 to 40 years (M=23.76, SD=4.79) were recruited from a Turkish speaking community. Participants were recruited through online surveys, and face-to-face distributions at Eastern Mediterranean University. Results showed that authoritarian and authoritative parenting, and delay of gratification significantly predicted social media dependency. However, narcissism, age, gender and permissive parenting style were not significant predictors. Findings indicated the importance of parental practices, and delay of gratification for the prevention of social media dependency.Öz.Sosyal medya bağımlılığı dünya genelinde popülerleşen bir araştırma konusudur. Güncel olarak, araştırmaların çoğu sosyal medya bağımlılığını, madde ve kumar bağımlılığı gibi davranışlarla karşılaştırmaktadır. Ancak, kişilik farklılıklarının sosyal medya bağımlılığı üzerindeki etkisini inceleyen araştırmaların sayısı yeterli seviyede değildir. Bu yüzden, bu çalışmanın ana amacı narsisizm, haz ertelemesi, ve algılanan ebeveynlik tarzının sosyal medya bağımlılığı üzerindeki yordayıcı etkisini araştırmaktır. Çalışma Türkçe konuşan, 18 ile 40 yaş (M=23.76, SD=4.79) arasında, 152 kadın ve 146 erkek katılımcı ile yürütülmüştür. Veriler çevrimiçi şekilde, ve Doğu Akdeniz Üniversitesi’nde yüzyüze dağıtılan anketlerle toplanmıştır. Sonuçlar otoriter ve yetkili ebeveynlik tarzının, ve haz erteleme becerisinin sosyal medya bağımlılığını anlamlı düzeyde yordadığını göstermiştir. Diğer yandan; narsisizm, izin verici ebeveynlik tarzı, yaş ve cinsiyet değişkenleri ile sosyal medya bağımlılığı arasında anlamlı bir ilişki bulunmamıştır. Bulgular ebeveynlik tarzlarının ve haz erteleme becerisinin sosyal medya bağımlılığını önlemede önemli değişkenler olduğunu düşündürmektedir.
Master of Science in Developmental Psychology. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Psychology, 2015. Supervisor: Assist. Prof. Dr. Fatih Bayraktar.
Keywords: Psychology; Developmental Psychology; narcissism - Social Media; Dependency; Social Media; Delay of Gratification; Narcissism; Parenting Style